A Systematic Literature Review on Islamic Expenditures - Sobiyanto, Ahmad; Bustamil, Bustamil; Handayani, Tri; Hamzah, Muhammad Zilal (El Barka: Journal of Islamic Economics and Business, 2023)
The purpose of this study is to identify past research trends on Islamic spending, evaluate research collaborative relationships, and identify future research directions.It uses 14 articles published between 2003-2022 about Islamic Expenditures indexed in Scopus (Q1-Q4) using a qualitative and quantitative approach, the Bibliometric method and Systematic Literature Review (SLR). This study uses VosViewers software and Publish or Perish. It is known that the author who has the most publications on Islamic Expenditure is U.H. Umar. The article with the most citations was the article entitled "A proposed model for waqf financing public goods and mixed public goods in Malaysia". The journal with the largest number of publications is the International Journal of Islamic and Middle Eastern Finance and Management. The countries that contributed the most to the release were Malaysia, Nigeria and Pakistan. This study makes several contributions, including for future researchers, the research results can be used as a reference to identify influential authors, articles, journals, countries, findings and methods. For researchers, the results of this study can be used as a benchmark and literature necessary for the development of Shariah consumer research and to reassess the gaps in Islamic cost or cost research.